A new hybrid multilevel inverter topology with harmonics profile improvement - Ayob, S. M. (2005)
A new hybrid multilevel inverter topology with harmonics profile improvement is presented in this paper. From the literature, it is agreed that hybrid multilevel inverter with its DC sources configured in trinary fashion presents the largest output levels and the lowest Total Harmonics Distortion (THD) percentage. However the output contains low order harmonics due to the impossibility of modulating all adjacent voltage levels at high frequency. With this proposed topology, all adjacent voltage levels are possible to be modulated at high frequency. As a result, the output voltage waveform presents better harmonics profile. The proposed topology and its modulation scheme are presented and verified with simulation results.